Predicting soil phosphorus buffer coefficients using potential sorption site density and soil aggregation - Wang, X.; Jackman, J.M.; Yost, R.S.; Linquist, B.A. (Wiley, 2000)
The phosphorus (P) buffer coefficient, a ratio of the increase in extractable P to the amount of applied fertilizer P, is a source of considerable uncertainty in determining the amount of fertilizer needed to meet crop P requirements. The use of clay as a predictor of the P buffer coefficient has been suggested for soils of similar mineralogy. However, it has not been satisfactory for soils with a wide range of soil mineralogies but relatively high clay content. The objective of this study was to improve the prediction of buffer coefficients using soil characteristics associated with the process of P sorption, such as mineralogy, surface area, and aggregation. The soil P sorption site density, estimated from detailed clay mineralogy, and reactive mass, the fraction of the total soil mass in the surface aggregates where newly added P can be sorbed, were used to predict the buffer coefficient. The P buffer coefficients of 10 soils with a wide range in P sorption were estimated by Mehlich 3, modified Truog, and 0.5 M NaHCO3 extractants for incubation periods of 32 and 180 d. The inclusion of P sorption site density and reactive mass substantially improved predicting the P buffer coefficients when compared with the P buffer coefficients predicted by only soil clay content. Statistical models showed that the P buffer coefficients were negatively correlated with both log of the P sorption site density and reactive mass. Thus, soils with fewer P sorption sites, lower reactive mass, and larger aggregate size will tend to have higher buffer coefficients, indicating that a greater portion of the added P remains plant available.